Analysis of tilt‐buckling of euler columns with varying flexural stiffness using homotopy perturbation method - Coşkun, Safa Bozkurt (Mathematical Modelling and Analysis, 2010)
In this paper, the Homotopy Perturbation Method (HPM), is introduced for elastic stability analysis of tilt‐buckled columns with variable flexural stiffness. Buckling loads and corresponding mode shapes are determined considering different types of variations in flexural stiffness of columns. The proposed approach is an efficient technique for the elastic stability analysis of specified problems.First published online: 09 Jun 2011